EFFECT OF REGIONAL ORIGINAL INCOME ON GOVERNMENT EXPENDITURE IN MAKASSAR CITY - Jam'an, Jam'an; Rizal, Samsul; Arsyad, Nur Fadilah (Jurnal Ekonomi Balance, 2020)
The main problem in this research is to know the description of the original regional income of the city of Makassar, to know the description of government expenditure in the city of Makassar, and to determine the effect of local revenue on government spending in the city of Makassar.This type of research is quantitative research. The research sampling technique was the last five years from 2015-2019. Data collection was carried out by documentation and literature study. The data collected in the study were analyzed using simple linear regression analysis techniques. Based on the results of data analysis, it can be seen that the data on local revenue and government expenditure have increased each year. The effect of local revenue on government spending is 0.296> 0.05. This means that local revenue has a positive but insignificant effect on government spending. The result of the determinant test (R2) in research X1 was 0.347 or 34.7%, while 65.3% was influenced by other factors. Based on these data, it can be concluded that there is no positive effect of local revenue on government spending in the city of Makassar.